The spider orchid trapped in its molecular web: Phylogeny and morphological evolution of the orchid genera Bartholina and Holothrix (Orchidaceae: Orchidoideae). Issue 5 (21st November 2019) - Le Péchon, Timothée; Johnson, Steven D.; Bytebier, Benny
Abstract: The orchid flora of southern Africa is taxonomically well‐known, although the phylogenetic relationships within and between several emblematic genera remain poorly understood. A case in point are the morphologically related genera Bartholina (2 spp.)—also known as spider orchids—and Holothrix (ca. 46 spp.) (Orchidaceae: Orchidoideae: Orchidinae). In this paper, we reconstructed phylogenetic relationships for those two orchid genera. We sequenced one nuclear (ITS) and two plastid ( trnL + trnL‐F, matK ) DNA regions, for 62 accessions, representing 29 species (out of 48 species, 60%) of the Holothrix / Bartholina alliance. The concatenated matrix included 3507 molecular characters and was analyzed using maximum likelihood, Bayesian inference, and parsimony. Our results showed that Holothrix is paraphyletic, with Bartholina nested within Holothrix . We identified five monophyletic lineages, strongly supported by molecular data, and several morphological synapomorphies that will form the basis of a new infrageneric classification. Furthermore, the phylogenetic tree clarified the taxonomy of the Holothrix villosa species complex and showed that H. villosa var. condensata is best treated at the rank of species.